2016
DOI: 10.3386/w21884
|View full text |Cite
|
Sign up to set email alerts
|

Cables, Sharks and Servers: Technology and the Geography of the Foreign Exchange Market

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Similar to a study by Griliches (1957), we describe a diffusion process with three parameters: the initial conditions, which we observe; the speed of diffusion, which we infer from the data; and the ultimate endpoint, which we posit. 1 The closest work to ours is that of Eichengreen et al (2016) who found that submarine fiber optic cables led to the loss of market share of the home foreign exchange market and the gain of offshore centers. In light of these findings, Mehl (2017) interpreted the euro area's loss of market share in trading the euro against other currencies and London's parallel gain as reflecting "London's trading cables."…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Similar to a study by Griliches (1957), we describe a diffusion process with three parameters: the initial conditions, which we observe; the speed of diffusion, which we infer from the data; and the ultimate endpoint, which we posit. 1 The closest work to ours is that of Eichengreen et al (2016) who found that submarine fiber optic cables led to the loss of market share of the home foreign exchange market and the gain of offshore centers. In light of these findings, Mehl (2017) interpreted the euro area's loss of market share in trading the euro against other currencies and London's parallel gain as reflecting "London's trading cables."…”
Section: Introductionmentioning
confidence: 87%
“…London's particular strength in FX can be ascribed to its time zone advantage. 4 Over time, the share of offshore trading in currencies has tended to rise; see McCauley and Scatigna (2011), Ehlers and Packer (2013), Eichengreen et al (2016) and Mehl (2017).…”
mentioning
confidence: 99%
“…They find that as Internet penetration in a partner country increases by 10 percent, service exports growth increases by 1.1 percentage points and import growth by 1.1 percentage points. Eichengreen et al (2016) focus on the foreign exchange market and find that greater connectivity via undersea cables dampens the impact of spatial frictions, by up to 80 percent, between local markets and major financial centers and increases offshore trading by 21 percent.…”
Section: Page 3 Of 34mentioning
confidence: 99%
“…Eichengreen, Lafarguette, and Mehl () point to the importance of geography: to whether a second‐tier financial center is close to one of the three financial hubs (London, New York, and Tokyo) where the electronic trading platforms of Thomson‐Reuters and Electronic Broking Services are located. Electronic traders, they observe, seek to limit latency time, which increases with distance from the platform .…”
Section: Related Literaturementioning
confidence: 99%
“…They highlight the advantages of a network of information and communications links for completing a high volume of financial transactions and thereby reaping economies of scale (Lee, Alford, Cresson, & Gardner, ). They single out geography as a factor influencing access to that network (Eichengreen, Lafargette, & Mehl, ). They emphasize the information content of financial assets—whether securities are information sensitive, in which case they are apt to be traded in multiple centers close to their originators, or information insensitive, in which case trading is more likely to concentrate in a small handful of venues to leverage thick‐market externalities (Gehrig, ).…”
Section: Introductionmentioning
confidence: 99%